2017
DOI: 10.1515/bhk-2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

College students’ perceptions of a caring climate in group physical activity classes

Abstract: SummaryStudy aim: Research suggests that physical activity rates decline sharply after high school. The pattern of activity or inactivity during college tends to persist into adulthood. A critical need exists for examination of strategies to engage college-age students in physical activity habits. One way to do this is through physical activity courses offered in colleges. This study examines the relationship between perceptions of a caring psychological climate and group connectedness, enjoyment, and attitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
2
0
1
Order By: Relevance
“…A caring climate, valuing the collective well-being, inspires more forms of active trust towards the top manager and peers, which promotes commitment to the organization [10]. Research, who found that perceptions of a caring climate were significantly related to enhancing feelings of group connectedness, heightened enjoyment, and more positive attitudes toward classmates and instructors [14]. This finding makes them suggest that a strategy to foster engagement in physical activity courses on campus is to train instructors to value, support, and welcome students.…”
Section: Caring Climatementioning
confidence: 99%
“…A caring climate, valuing the collective well-being, inspires more forms of active trust towards the top manager and peers, which promotes commitment to the organization [10]. Research, who found that perceptions of a caring climate were significantly related to enhancing feelings of group connectedness, heightened enjoyment, and more positive attitudes toward classmates and instructors [14]. This finding makes them suggest that a strategy to foster engagement in physical activity courses on campus is to train instructors to value, support, and welcome students.…”
Section: Caring Climatementioning
confidence: 99%
“…Studies to date have shown that the motivational climate generated by the teacher and classmates has a significant influence on student engagement and participation during PE lessons ( Newland et al, 2017 ; Zach et al, 2020 ). However, it is necessary to take into consideration students’ perceived satisfaction with the teacher’s teaching methodology and its influence on the students’ learning process ( Kosiba et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…En el análisis, la motivación se refiere a aquellos factores de la personalidad, variables sociales y cogniciones que entran en juego cuando la persona realiza una tarea. Aunque puede haber prioridad de unas razones sobre otras, la naturaleza multifacética de este constructo expone la existencia múltiple de ellas para viajar y hacer ejercicio en el medio natural (Newland, Newton, Stark, Podlog & Hall, 2017). De forma semejante, afirman Weed y Bull (2004), en la práctica deportiva intervienen varios impulsos, por ejemplo: la recuperación psicológica, el escape a la rutina diaria y el sentimiento de libertad.…”
Section: Introductionunclassified